Quantifying lamina-controlled variations in rock physical properties from AI-reconstructed 3D multimineral digital rocks - Yuqi Wu; Yumei Ao; Jiabao Yang; Zijie Lu; Keyu Liu; Yuchen Fan; Jianhua Zhao; Li Hou; Bo Liao; Pejman Tahmasebi (International Journal of Rock Mechanics and Mining Sciences, 2026)

Bacteria-inspired mechano-chemical nanovaccines enable multi-activation of dendritic cells for potent antitumor immunity - Hongjuan Zhao; Chenxi Zhao; Yuting Cang; Jinpei Sun; Qing Li; Keyu Zong; Yajing Wang; Di Meng; Qingling Song; Lei Wang (Chemical Engineering Journal, 2026)

Numerical study on the dynamic characteristics of high-pressure hydrogen-oxygen premixed flame in combustion light gas gun - Junjie Lu; Qiuyang Zhao; Keyu Zhao; Tengyu Li; Yechun Wang; Hui Jin; Liejin Guo (Fuel, 2026)

Mineralization of calcium phosphate regulated by a Zr-based MOF on its surface for the removal of beryllium from Be-containing wastewater - Xu Zhao; Zhengyang Shan; Keyu Zhu; Yige Sun; Qingliang Wang; Xiujuan Feng (Chemical Engineering Journal, 2026)

High-frequency redox fluctuations in deep-lacustrine basin and their impact on organic carbon burial: Records from micrometer-scale laminae in the Triassic Yanchang Formation Shale, Ordos Basin - Ke Li; Kelai Xi; Yingchang Cao; Zhe Zhao; Xiujuan Wang; Miruo Lin; Keyu Liu; Fang Hao (Science China Earth Sciences, 2026)

Diagenetic evolution of clay minerals and impacts on reservoir quality of the Wufeng and Longmaxi Shale in Sichuan Basin of China - Yang Chen; Jianhua Zhao; Qinhong Hu; Keyu Liu; Mengxiang Yu; Wei Wu; Chao Luo (Applied Clay Science, 2026)

Synergistic effects of pyrite and sludge biochar enhancing performance and reducing greenhouse gas emissions in constructed wetland-microbial fuel cells - Wang Maosen; Qin Yangyi; Wu Haiming; Zhao Jianguo; Zheng Lihe; Ding Keyu; Wang Baogui; Du Jingjing (Bioresource Technology, 2026)

Effects of aerosol decline on surface solar radiation during the implementation period of air pollution prevention and control policies over China - Keyu Zhao; Henan Han; Junyan Chen; Guozheng Liu; Tiegang Liu (Journal of Hazardous Materials, 2026)

Seismic-attribute optimization for improving reservoir prediction integrating the spectral decomposition and automated machine learning - Keyu Ren; Wei Li; Lun Zhao; Wurong Wang; Jincai Wang; Han Wang; Yi Li; Linbo Qu; Dali Yue (Journal of Applied Geophysics, 2026)

Larix gmelinii growth limitation shifts from nitrogen availability to drought under warming and permafrost degradation - Zecheng Chen; Binqing Zhao; Wenqi Song; Hans W. Linderholm; Jan Altman; Keyu Zhang; Hanjun Dong; Xinran Huang; Haoyuan Chen; Xiaochun Wang (Global and Planetary Change, 2026)

Dietary lard promotes intramuscular fat deposition via gut microbiota-taurine axis in rabbits - Jiahao Shao; Liwen Guo; Keyu Niu; Yanjie Zhang; Herui Cao; Yongju Zhao (Food Bioscience, 2026)

Alkali–organic synergy rewires microbial acid tolerance to restore nitrogen cycling in acidic soils - Mengke Li; Keyu Yao; Jean Damascene Harindintwali; Min Qian; Nan Wu; Yanwei Kan; Ziyi Song; Xian Xiao; Peng Liu; Yuan Zhao (Journal of Environmental Management, 2026)

Developmental stage-specific disruption of iron allocation by a ZmYSL2 mutation in maize - Yikai Wang; Kunfeng Zhang; Chuang An; Jiayi Liu; Hongmei Hu; Duo Shi; Jiaxin Shi; Keyu Zhao; Dan Liu; Ling Wu; Xiao Zhang; Bowen Luo; et al. (Planta, 2026)

Spatiotemporal variations of rainfall interception before and after implementation of Grain for Green Program in the Loess Plateau - Junyan Chen; Guozheng Liu; Jing Wu; Keyu Zhao; Tiegang Liu (Journal of Hydrology, 2026)

Mechanisms of montmorillonite-mediated high-temperature catalysis of organic matter under variable hydration states and implications for petroleum geology - Xiaoyang Zhao; Guanghui Yuan; Yingchang Cao; Fang Hao; Keyu Liu; Zihao Jin; Xiaohan Fu; Fulin Shao (Science China Earth Sciences, 2026)

Antisolvent sequence as a tunable switch for zein-naringin-D-tocopheryl polyethylene glycol 1000 succinate (TPGS) nanoparticles: interfacial dynamics and bioactivity enhancement - Yitong Wang; Keyu Qiu; Ruizi Zhou; Shuxian Bai; Chao Ai; Yanan Zhao; Jesus Simal-Gandara; Hui Teng; Lei Chen (Food Chemistry, 2026)

Unraveling the drivers of corn yield response to optimization fertilization in plateau acidic red soils - Zhengfa Chen; Keyu Yan; Hui Yan; Xiaohan Mei; Chi Wang; Xingwei Chen; Wanli Hu; Bin Fu; Ming Ni; Zhiwu Li; Qingsong Duan; Yanmei Hu; et al. (Field Crops Research, 2026)

Regional disparities and provincial peak trajectories of transportation carbon emissions in Western China - Zhixiao Zhang; Keyu Wen; Hao Gong; Yugang Wang; Liuhui Zhao; Dongmei Wang; Zhengjun Gong (Transportation Research Part D: Transport and Environment, 2025)

In vitro gastrointestinal digestibility under infant conditions of bovine milk fat emulsions stabilized using decalcified micellar casein concentrate - Keyu Wang; Yuhan Zhao; Wenzhu Yin; Dasong Liu; Xiumei Tao; Yimiao Wang; Thom Huppertz; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Hydrocolloids, 2025)

Delayed progression of diabetic cataractogenesis and retinopathy by topical administration of highly biocompatible carbon dots derived from Scutellaria barbata and Herba hedyotis diffusae - Jiawei Wang; Yihan Zhao; Xueying Yang; Can Li; Keyu Liu; Chenzhao Ma; Yanyan Jiang; Jianqiao Li (Chemical Engineering Journal, 2025)

Paleoenvironment and organic matter enrichment in the Kaijiang–Liangping Trough across the Emeishan Large Igneous Province (ELIP) - Mengxiang Yu; Jianhua Zhao; Keyu Liu; Qinhong Hu; Wei Wu; Quanyou Liu; Chao Luo; Yang Chen; Hongyu Ma; Zhijun Jin (Marine and Petroleum Geology, 2025)

The synergistic effect of triazine-N and secondary amine-N anchors iodine species with MXene composite cathode for stable aqueous Zn–I2 battery - Jing Ma; Yaoyao Linghu; Kai Yuan; Rui Zhou; Hui Gao; Peihua Zhao; Shaohui Guo; Huiqi Wang; Yongping Qu; Chao Shen; Keyu Xie (Chemical Engineering Journal, 2025)

Sediment remediation by La-MOF/PP fabric coupled with phosphate solubilizing bacteria: Phosphate activation and removal - Qinqin He; Wenhao Lu; Hang Zhou; Xiaonan Ji; Wei Hu; Kuo Pang; Zedong Teng; Xin Zhao; Lintao Wang; Keyu Fan; Feichao Hu; Min Li (Journal of Environmental Chemical Engineering, 2025)

Oxygen vacancies and Li+ pre-embedding for magnesium storage in Anatase TiO2 toward magnesium/lithium hybrid batteries - Haofei Du; Xueyang Hou; Fan Cheng; Yifan Liu; Zhao Fang; Keyu Xie; Ling Zhang (Chemical Engineering Journal, 2025)

An enhanced nitrate-to-ammonia conversion through bimetallic synergism and architectural effects - Yuyue Zhu; Keyu Zhou; Donglin Zhao; Huiying Li; Guangyin Fan; Pengyao You (Journal of Environmental Chemical Engineering, 2025)

Thermally driven organic-inorganic interactions in sedimentary basins: A review from source rocks to reservoirs - Guanghui Yuan; Yingchang Cao; Zhijun Jin; Hans-Martin Schulz; Zihao Jin; Rui Fang; Xiaoyang Zhao; Keyu Liu; Jixuan Wang (Earth-Science Reviews, 2025)

Changes in soil inorganic carbon following vegetation restoration in the cropland on the Loess Plateau in China: A meta-analysis - Zhenyu Zhao; Keyu Ren; Yang Gao; Mengfan Zhao; Long Zhou; Shaofeng Huo; Jiabin Liu (Journal of Environmental Management, 2024)

Crystal and micro-nano structure bidirectional regulation of iron oxalate for high-lithium storage and ultralong-cycling life via ultrasound assistance - Qing Zhao; Keyu Zhang; Geng Gao; Bo Jin; Guangping Zi; Rui Yan; Binbin Li; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Development of a CRISPR/Cas12a-based method to detect invasive aquatic species - Minlin Zhang; Xiaoling Zuo; Jiantao Liang; Keyu Lu; Liyun Wei; Xu Yan; Huihong Zhao; Songyong Gan; Jinhui Wu; Qing Wang (Aquaculture, 2024)

Petaloid CoP/FeP Composites: Efficiently bifunctional cathode electrochemical oxygen catalysts for aqueous and Solid-State Zinc-Air batteries - Keyu Chen; Lu Wang; Jilan Long; Fei Zhao; Li Kang (Chemical Engineering Journal, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Investigation on Phenomics of Traditional Chinese Medicine from the Diabetes - Boxun Zhang; Lijuan Zhou; Keyu Chen; Xinyi Fang; Qingwei Li; Zezheng Gao; Fengmei Lian; Min Li; Jiaxing Tian; Linhua Zhao; Xiaolin Tong (Phenomics, 2024)
With thousands of years of application history, traditional Chinese medicine (TCM) has unique advantages in the prevention of various chronic diseases, and in recent years, the development of TCM has presented a situation where opportunities and challenges coexist. Phenomics is an emerging area of life science research, which has numerous similarities to the cognitive perspective of TCM. Thus, how to carry out the interdisciplinary research between TCM and phenomics deserves in-depth discussion. Diabetes is one of the most common chronic non-communicable diseases around the world, and TCM plays an important role in all stages of diabetes treatment, but the molecular mechanisms are difficult to elucidate. Phenomics research can not only reveal the hidden scientific connotations of TCM, but also provide a bridge for the confluence and complementary between TCM and Western medicine. Facing the challenges of the TCM phenomics research, we suggest applying the State-target theory (STT) to overall plan relevant researches, namely, focusing on the disease development, change trends, and core targets of each stage, and to deepen the understanding of TCM disease phenotypes and the therapeutic mechanisms of herbal medicine.

Occurrence of ochratoxin A in Sichuan bacon from different geographical regions and characterization and biocontrol of ochratoxigenic Aspergillus westerdijkiae strain 21G2-1A - Kaidi Hu; Keyu Guo; Xingjie Wang; Song Wang; Jianlong Li; Qin Li; Ning Zhao; Aiping Liu; Li He; Xinjie Hu; Yong Yang; Likou Zou; et al. (Food Research International, 2024)

Integration of hydrothermal liquefied sludge as wastewater for anaerobic treatment and energy recovery: Aqueous phase characterization, anaerobic digestion performance and energy balance analysis - Changhao Liu; Zhengbo Yue; Ding Ma; Keyu Li; Pengcheng Zhao; Manyi Yang; Jin Wang (Journal of Water Process Engineering, 2024)

Multi objective optimization of recycled aggregate concrete based on explainable machine learning - Shiqi Wang; Peng Xia; Fuyuan Gong; Qiang Zeng; Keyu Chen; Yuxi Zhao (Journal of Cleaner Production, 2024)

Comparison analysis of microbial agent and different compost material on microbial community and nitrogen transformation genes dynamic changes during pig manure compost - Naiyuan Liu; Zhuangzhuang Liu; Keyu Wang; Jinfeng Zhao; Jun Fang; Gang Liu; Hao Yao; Junting Pan (Bioresource Technology, 2024)

Long-term grazing exacerbates soil microbial carbon and phosphorus limitations in the desert steppe of Inner Mongolia - A study based on enzyme kinetics - Shaoyu Li; Bin Zhang; Yanan Li; Tianqi Zhao; Jiahua Zheng; Jirong Qiao; Feng Zhang; Carlo Fadda; Devra Jarvis; Nadia Bergamini; Keyu Bai; Zongwen Zhang; et al. (Applied Soil Ecology, 2024)

Revealing the infiltration process and retention mechanisms of surface applied free DNA tracer through soil under flood irrigation - Geng Liu; Linxi Guo; Chaozi Wang; Jiarong Liu; Zengjie Hu; Helen E. Dahlke; En Xie; Xiao Zhao; Guanhua Huang; Jun Niu; Keyu Fa; Chenglong Zhang; et al. (Science of The Total Environment, 2023)

Crystallinity and formation of silica in Palaeozoic shales: A new quantification calculation method based on X-Ray diffraction - Guoheng Liu; Keyu Liu; Gangyi Zhai; Jianhua Zhao; Zongguang Guo (Marine and Petroleum Geology, 2023)

Responses of grassland productivity to mowing intensity and precipitation variability in a temperate steppe - Feng Zhang; Jonathan A. Bennett; Bin Zhang; Tianqi Zhao; Keyu Bai; Mengli Zhao; Guodong Han (Oecologia, 2023)

A three-dimensional experimental study on bank retreat: The coupled role of seepage and surface flow - Keyu Wang; Zheng Gong; Kun Zhao; Shuai Tang; Kaili Zhang (Frontiers in Marine Science, 2022)
The coupled role of seepage and surface flow on bank retreat has long been neglected, partly due to the concealment and complexity of seepage erosion. To fill this gap, we set up a three-dimensional laboratory experiment to explore bank retreat process in response to seepage and surface flow. During each experiment, we measured the changes of total soil stress, matric suction, and water content within the bank, as well as flow velocity and suspended sediment concentration near the bank. Results show that a rapid decrease in matric suction, the bank toe undercutting consequent to seepage erosion, the formation of tension crack on the bank top, and the occurrence of toppling or shear failure is the typical sequence of the observed bank retreat process under seepage flow. The inclusion of surface flow erodes slump blocks and so promotes cantilever formation, leading to additional bank failure. Compared with the case where only seepage is considered, the frequency of toppling failure under the coupled effect of seepage and surface flow decreases, but the contribution to the bank retreat increases by 37 %. The time taken to collapse in three-dimensional experiments is at least 1.5 h earlier than that of two-dimensional experiments, indicating the importance of preferential flow pathways of seepage. Overall, this research illustrates how surface flow interacts with seepage flow to control bank retreat process and is indeed a first step toward a fully understanding of multifactor-driven bank retreat.

Occurrence and distribution characteristics of antibiotic resistance genes in sediments between urban and rural of the Liaohe River Basin, China - Guangshui Na; Keyu Zhang; Hui Gao; Ruijing Li; Shuaichen Jin; Fuqiang Zhao; Haibo Zhang; Shisheng Li (Environmental Science and Pollution Research, 2021)

Multi-model ensemble simulated non-point source pollution based on Bayesian model averaging method and model uncertainty analysis - Huiliang Wang; Keyu Lu; Yulong Zhao; Jinxia Zhang; Jianli Hua; Xiaoying Lin (Environmental Science and Pollution Research, 2020)

Roles of sulfur compounds in growth and alkaline phosphatase activities of Microcystis aeruginosa under phosphorus deficiency stress - En Xie; Fangfang Li; Chaozi Wang; Wei Shi; Chen Huang; Keyu Fa; Xiao Zhao; Dayi Zhang (Environmental Science and Pollution Research, 2020)

Identified trans-splicing of YELLOW-FRUITED TOMATO 2 encoding the PHYTOENE SYNTHASE 1 protein alters fruit color by map-based cloning, functional complementation and RACE - Lulu Chen; Wenzhen Li; Yongpeng Li; Xuechao Feng; Keyu Du; Ge Wang; Lingxia Zhao (Plant Molecular Biology, 2019)

Determination of the thicknesses of oil films in micro- and nano-pores in tight oil sands: an example from the southern Songliao Basin, NE China - Yanjie Gong; Keyu Liu; Meng Jun Zhao (Arabian Journal of Geosciences, 2017)

Replicative senescence of human bone marrow and umbilical cord derived mesenchymal stem cells and their differentiation to adipocytes and osteoblasts - HuanChen Cheng; Lin Qiu; Jun Ma; Hao Zhang; Mei Cheng; Wei Li; Xuefei Zhao; Keyu Liu (Molecular Biology Reports, 2011)